2006
DOI: 10.1136/bjo.2005.083733
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of age related eye diseases in Asia

Abstract: In the past decade, several large population based studies have provided new information on the prevalence of visual impairment and the major age related eye diseases in Asia. These include epidemiological studies from India, Taiwan, Mongolia, Singapore, and Japan. In particular, the epidemiology of refractive errors and glaucoma has been well characterised, providing insights not only into the public health implications of these conditions, but also into anatomical changes of the eye with ageing. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(184 citation statements)
references
References 77 publications
(72 reference statements)
4
173
1
Order By: Relevance
“…Recent studies reported that in Asia myopia rates varied widely between urban and rural populations. 15,16 In Taiwan, compared with schoolchildren living in towns or villages, those living in cities had much higher myopic refraction. 3 Consistently, our study showed that degrees of urbanization were strongly associated with myopia, particularly in the age groups of 20-39 and 40-64 years.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that in Asia myopia rates varied widely between urban and rural populations. 15,16 In Taiwan, compared with schoolchildren living in towns or villages, those living in cities had much higher myopic refraction. 3 Consistently, our study showed that degrees of urbanization were strongly associated with myopia, particularly in the age groups of 20-39 and 40-64 years.…”
Section: Discussionmentioning
confidence: 99%
“…In [9], histogram based analysis of the color pixel intensity together with multiple method fusion are also employed to further improve cup detection accuracy. Table 1 compares our method to these two level-set approaches 1 .…”
Section: Comparison With Level-set Based Segmentation [6][9]mentioning
confidence: 99%
“…Glaucoma affects about 60 million people [1] and is responsible for approximately 5.2 million cases of blindness (15% of world total) [2]. It unfortunately cannot be cured because the damage to the optic nerve cannot be reversed.…”
Section: Introductionmentioning
confidence: 99%
“…34 In recent years, there have been several well-conducted studies on the epidemiology of glaucoma in Asian people indicating that the prevalence of glaucoma ranges from 2.1% to 5.0%. 35 Inferring from these data, it is estimated that approximately 1.05% to 2.5% of the population has undetected glaucoma. This small number of patients with undetected glaucoma would be categorized as nonglaucoma and would have a small chance of being selected as part of the comparison cohort.…”
Section: Ho Et Al Open-angle Glaucoma and Strokementioning
confidence: 99%